Genetic diversity and phylogenetic relationships in the rye genus Secale L. (rye) based on Secale cereale microsatellite markers - Shang,Hai-Ying (2006)
The genetic diversity and phylogenetic relationships in the genus Secale L. (rye) was evaluated using 24 Secale cereale microsatellite (SCM) markers. The average polymorphism information content (PIC) value of each microsatellite locus in 30 Secale accessions evaluated was higher than that in 47 cultivated ryes (Secale cereale ssp. cereale). The mean genetic similarity (GS) index in Secale was lower than that in cultivated rye. The highest within-species GS index was observed for S. sylvestre and the lowest for S. strictum, whereas the highest between-species GS index was found between S. cereale and S. vavilovii and the lowest between S. sylvestre and S. cereale. There was no obvious difference in GS levels in the cultivated rye accessions from Asia, Europe, North America or South America. Cluster analysis indicated that all the Secale accessions could be distinguished by the 24 microsatellite loci. We also found that the S. sylvestre accessions were obviously divergent from the accessions of other species and that the S. vavilovii accessions were closely related to the S. cereale accessions. Our results also showed that S. strictum was heterogeneous and showed great within-species differences. The microsatellite-derived dendrogram faithfully reflected the phylogenetic relationships between Secale species but did not indicate a possible domestication process of the cultivated rye based on the geographical sources of the accessions.